2015
DOI: 10.1038/ncomms7764
|View full text |Cite
|
Sign up to set email alerts
|

Mir-17–92 regulates bone marrow homing of plasma cells and production of immunoglobulin G2c

Abstract: The polycistronic mir-17-92 cluster, also known as oncomir-1, was previously shown to be essential for early B lymphopoiesis. However, its role in late-stage B-cell differentiation and function remains unexplored. Here we ablate mir-17-92 in mature B cells and demonstrate that mir-17-92 is dispensable for conventional B-cell development in the periphery. Interestingly, mir-17-92-deficiency in B cells leads to enhanced homing of plasma cells to the bone marrow during T-cell-dependent immune response and selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…A study examining the functional role of the miR-17~92 cluster in late B cells revealed its potential importance in plasma cells [62] (thus, important not only in early B cell development and tolerance [30, 31, 40]). Indeed, conditional deletion of this cluster in mature B cells using CD19-Cre mice resulted in increased plasma cell homing to the BM upon immunization with a T-independent antigen, suggesting that this miRNA cluster regulated homing of plasma cells to their natural niche [62].…”
Section: Mirnas In Terminal Differentiation Of B Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…A study examining the functional role of the miR-17~92 cluster in late B cells revealed its potential importance in plasma cells [62] (thus, important not only in early B cell development and tolerance [30, 31, 40]). Indeed, conditional deletion of this cluster in mature B cells using CD19-Cre mice resulted in increased plasma cell homing to the BM upon immunization with a T-independent antigen, suggesting that this miRNA cluster regulated homing of plasma cells to their natural niche [62].…”
Section: Mirnas In Terminal Differentiation Of B Cellsmentioning
confidence: 99%
“…Indeed, conditional deletion of this cluster in mature B cells using CD19-Cre mice resulted in increased plasma cell homing to the BM upon immunization with a T-independent antigen, suggesting that this miRNA cluster regulated homing of plasma cells to their natural niche [62]. Speciffically, the data indicated that the sphingosine 1-phosphate receptor 1 (S1PR1), a receptor for S1P, was a target of different members of the miR-17~92 cluster in B cells [62]. The S1PR1-S1P signaling pathway had been previously shown to be critical for immune cell migration from secondary lymphoid organs to the BM [63].…”
Section: Mirnas In Terminal Differentiation Of B Cellsmentioning
confidence: 99%
See 3 more Smart Citations